Sensor technologies in monitoring of civil engineering structures - Zawawi, Umi Adzmira (2006)
This paper describes and reviews various sensor technologies, particularly fiber-optic sensor, which are applicable to the monitoring of civil engineering structures. Aspects of review include technical requirement, design and fabrication, and instrumentation procedures for the sensors. A comparative study on the relative merits and selection criteria is carried out through an analysis of selected case studies on real applications of sensors in structures. The analysis provides some general guidelines on technical implementation of structural monitoring using those sensors for our local conditions. Finite Element Modelling (FEM) is carried out for case study III for comparison purpose. In general, it is found that the fiber optic sensors give a higher value of stress-strain compared to the conventional electrical resistance strain gauge. This is due to the properties of the electric strain gauge, which does not necessary capture the randomly developed crack or the steel reinforcement in the particular cracked zone. Fiber optic based sensors have superior properties for structural monitoring and are able to record strain readings even after member collapse.